1999
DOI: 10.1177/089686089901900210
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Hyaluronan Production in Stable Continuous Ambulatory Peritoneal Dialysis Patients

Abstract: Objective Several cytokines and proteins are excreted intraperitoneally during the course of peritonitis and stable states in continuous ambulatory peritoneal dialysis (CAPD) patients. Dialysate hyaluronan (HYA) is also regarded as a marker of peritoneal healing during bacterial peritonitis. We examined here, intraperitoneal HYA production in stable CAPD patients and compared the results to those of the peritoneal equilibration test (PET), the length of time on dialysis, and other marker proteins. Design We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 30 publications
0
31
1
Order By: Relevance
“…Morphological changes of the peritoneum can be identified via laparoscopy (114,115), peritoneal biopsy of the parietal wall (116), and cytological examination of mesothelial cells in drained PD solution (117), commonly displaying specific alterations. Humoral factors in the drained PD solution, such as cancer antigen 125, hyaluronic acid, matrix metaprotease‐2 (MMP‐2), interleukin‐6, vascular endothelial cell growth factor, and clotting and fibrinolytic factors, have been reported to be useful as markers of peritoneal deterioration (118–122). Moreover, there have been reports that an increase in the circulating β 2 ‐microglobulin level (123) and gene polymorphisms (124) are involved in tissue damage.…”
Section: Chapter 5: Discontinuation Of Peritoneal Dialysis To Avoid Ementioning
confidence: 99%
“…Morphological changes of the peritoneum can be identified via laparoscopy (114,115), peritoneal biopsy of the parietal wall (116), and cytological examination of mesothelial cells in drained PD solution (117), commonly displaying specific alterations. Humoral factors in the drained PD solution, such as cancer antigen 125, hyaluronic acid, matrix metaprotease‐2 (MMP‐2), interleukin‐6, vascular endothelial cell growth factor, and clotting and fibrinolytic factors, have been reported to be useful as markers of peritoneal deterioration (118–122). Moreover, there have been reports that an increase in the circulating β 2 ‐microglobulin level (123) and gene polymorphisms (124) are involved in tissue damage.…”
Section: Chapter 5: Discontinuation Of Peritoneal Dialysis To Avoid Ementioning
confidence: 99%
“…It is now becoming clear, however, that in addition to the acute effects of peritonitis, chronic local inflammation also is a feature of the peritoneal cavity of PD patients. Studies of inflammatory markers such as hyaluronic acid (HA) and IL-6 have demonstrated that their levels in the dialysis effluent increase with therapy duration [50,51]. Although the precise factors responsible for this apparent progressive rise in local inflammation are unclear, there is some preliminary evidence that it may be related to dialysis solution exposure [52].…”
Section: Understanding the Implication Of Increased Peritoneal Inflammentioning
confidence: 99%
“…These studies were seminal to our understanding of acute inflammation and underpin our current understanding of the control of these events [31,41]. At the same time, it was realized that evaluation of effluent markers in stable PD patients might also permit the description of inflammatory and fibrogenic changes that occur over time in the peritoneal membrane [51,[78][79][80].…”
Section: Ex Vivo Studies With New Solutions: Impact On the Peritonealmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic application of the addition of HA to PD fluid is based on the assumption that HA is lost from the peritoneal cavity during PD [ 97 ]. In PD patients, IP production of HA increases during episodes of peritonitis [ 41 , 98 ], and with the duration of PD therapy the HA concentration rises in the effluent of PD patients [ 99 ]. Consequently, the first animal studies were performed to determine the role of HA in peritoneal function during PD [ 97 ].…”
Section: Animal Studies On Pd Examining In Vivo Ha Applicationmentioning
confidence: 99%